Predictors of Injury and Reporting of Intraracial, Interracial, and Racially-Biased Nonsexual Assaults, United States, 2003-2011 - Socia, Kelly ([Verlag nicht ermittelbar], 2018)
These files are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. This study more thoroughly explored the unique nature of racially- and ethnically-motivated assaults than previous work focused on situational predictors, which was reliant on official statistics and lacked adequate comparison groups. The data for this study came from the National Crime Victimization Survey (NCVS) and the National Incident-Based Reporting System (NIBRS). Agency-level data from Law Enforcement Management and Statistics (LEMAS) augmented the NIBRS data for one part of the analyses. The NCVS contained self-reported incident-level crime data from a nationally representative victimization survey, while NIBRS contains officially-reported incident-level crime data. There are no data files available with this study; only syntax files used by the researchers are provided.